1998
DOI: 10.1002/1361-6374(199806)6:2<63::aid-bio1>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic fluorescence imaging of tissue selective lanthanide chelates

Abstract: Endoscopic probes have been incorporated into a fluorescent imaging system for the remote quantitation of tissue selective markers. Resolution at the level of 114 line pairs/mm allows visualization of regions that are approximately 6 mm wide. Tissue selective markers, based on polyazamacrocyclic chelates of terbium increase contrast and can be quantified in tissues at the sub‐picomole level. Minimally invasive in vivo fluorescence imaging is demonstrated. The potential for application of the system to disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…1.0 and 0.5 mmol/kg for TmDOTP 5À and TmDOTMA À , respectively), it is unlikely that conditions for renaly ligated rats ever reach fatal levels. However, biodistribution studies with lanthanide ion complexes (30,31) show that phosphonic acids deposit more favorably on bone, whereas carboxylic acids (because of their lower charge compared to phosphonic acids) have better access through the blood-brain barrier. Previously, we showed that TmDOTP 5À is observed in cerebral spinal fluid at mM level (32), and because of its high negative charge, proposed fenestrated vessels of circumventricular organs, not necessarily the blood-brain barrier, as the delivery route for entry into extracellular space (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1.0 and 0.5 mmol/kg for TmDOTP 5À and TmDOTMA À , respectively), it is unlikely that conditions for renaly ligated rats ever reach fatal levels. However, biodistribution studies with lanthanide ion complexes (30,31) show that phosphonic acids deposit more favorably on bone, whereas carboxylic acids (because of their lower charge compared to phosphonic acids) have better access through the blood-brain barrier. Previously, we showed that TmDOTP 5À is observed in cerebral spinal fluid at mM level (32), and because of its high negative charge, proposed fenestrated vessels of circumventricular organs, not necessarily the blood-brain barrier, as the delivery route for entry into extracellular space (29).…”
Section: Discussionmentioning
confidence: 99%
“…Waterbased MR methods for temperature depend on chemical shift changes observed by MRS (13) or by MRI using alterations in longitudinal relaxation time (14) or molecular diffusion coefficient (15). The most common MRS method for pH uses 31 P chemical shifts of endogenous inorganic phosphate (Pi) and phosphocreatine (PCr) (16). Other MRS methods rely on small nonparamagnetic exogenous agents, but have relatively lower sensitivity (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Other fluorescent biomaterials include fluorescent organic dyes such as cyanine, fluoresceins and rhodamines 5,6 as well as lanthanide chelates. 7 In this manner fluorescent quantum dots (QDs) are also good examples of new fluorescent biomaterials. [8][9][10][11] Introduction of QDs to biomedical applications was a tremendous improvement in labeling and bioimaging of many different processes in patients in cancer therapy and diagnosis.…”
mentioning
confidence: 99%